Characterization of the constituents in rat plasma after oral administration of radix polygoni multiflori extracts by ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry. (25th March 2015) - Lin, Longfei; Lin, Hongmei; Yin, Xingbin; Zhao, Yang; Xia, Zhenwen; Zhang, Miao; Li, Xuechun; Han, Jing; Qu, Changhai; Ni, Jian
Abstract An ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry method was established to detect as many constituents in rat plasma as possible after oral administration of Radix polygoni multiflori (RPM) extract. A C18 column (150 × 2.0 mm, 4 µm) was adopted to separate the samples, and mass spectra were acquired in negative modes. The fingerprints of RPM extract were established, resulting in 39 components being detected. Among these compounds, 29 were identified by comparing the retention times and mass spectral data with those of reference standards and relevant references, and eight compounds were separated and detected in RPM for the first time. In vivo, 23 compounds were observed in dosed rat plasma, 16 of 23 compounds were indicated as prototype components of RPM, and seven compounds were predicted to be metabolites of RPM. A high‐speed and sensitive method was developed and was successfully utilized for screening and characterizing the ingredients and metabolites of RPM. Copyright © 2015 John Wiley & Sons, Ltd.